A ética econômica das classes trabalhadoras: a gramática social do comportamento econômico da nova pequena burguesia comercial de Natal/RN - Freitas, Carlos Eduardo (2013)
Rogram relying on sociological interface between Economic Sociology, Sociology of Moral Theory of Socialization and Social Stratification, this dissertation research makes use of theoretical contributions Luic Boltanski, Charles Taylor, Axel Honneth, Pierre Bourdieu and Bernard Lahire to problematize the generally about the physical and symbolic production and social reproduction of the type of "economic ethics" predominant in the new petite bourgeoisie Brazilian. In other words, the goal is to explain and analyze the objective conditions (economic needs and moral grammar) and intersubjective (modes of socialization and social networks) and update the social genesis and contextual transcontextual beliefs, biases, inclinations and cultural regularities observed the economic behavior of individual profiles for the fractions of the urban petty bourgeoisie and commercial upward Natal / RN. With regard to methodological strategies adopted in data collection will be conducted qualitative interviews (semistructured) and ethnographic notes. In turn, the analytical treatment of the collected empirical content is based on the approach dispositionalist (Pierre Bourdieu, Loïc Wacquant and Bernard Lahire) that emphasizes the study of the past embedded agents and the different contexts of incorporation / activation / inhibition of "provisions" individual cultural